Comparison of three types of drying (supercritical CO2, air and freeze) on the quality of dried apple – Quality index approach. (August 2018) - Djekic, Ilija; Tomic, Nikola; Bourdoux, Siméon; Spilimbergo, Sara; Smigic, Nada; Udovicki, Bozidar; Hofland, Gerard; Devlieghere, Frank; Rajkovic, Andreja
Abstract: The aim of this study was to develop a quality index and examine the effects of drying apples using three technologies (supercritical CO2 drying, air drying and freeze drying) during a period of six months in ambient conditions. Based on nine quality parameters (textural, colour and sensory properties), a mathematical model for calculating a single total quality index (TQI) of dried apples packed in different types of packaging in normal and modified atmosphere has been introduced. At the beginning of the study, apples dried in supercritical CO2 had the best scores. After six months, samples dried in supercritical CO2 and freeze dried apples, both packed in polyethylene coated aluminium with 100% N2, scored similarly. The six month shelf-life research revealed that measurable changes occur during the second half of the shelf-life when it is possible to clearly distinguish differences in the overall quality index of different dried apple slices. Highlights: Quality deterioration of dried apples using three technologies was examined. Apples were packed in modified atmospheres and stored at 22 °C for six months. Quality function deployment method was used to assign quality weight factors. A total quality index has been introduced to evaluate the samples during shelf life.